Nurses' Motivation, Altruism and Professional Commitment Levels During the Pandemic: A Descriptive and Correlational Study - Aysel Özsaban; Nuray Turan; Yasemin Kıyak; Ayşen Karabacak; Gözde Ataş Türköz; Gizem Öner; Türkinaz Aştı (Sağlık ve Hemşirelik Yönetimi Dergisi)
Aim: This study aimed to examine the relationship between the motivation, altruism and professional commitment levels of nurses during the COVID-19 pandemic. Method: This descriptive and correlational study was conducted with 241 nurses working in a university hospital between January 2021 and January 2022. Data were collected using the Nurse Information Form, Nurse Job Motivation Scale, Altruism Scale and Nursing Professional Commitment Scale based on self-report. Results: The nurses included in this study had an average score of 66.56 (SD=7.70) on the Nurses Job Motivation Scale, 70.24 (SD=10.5) on the Altruism Scale, and 77.81 (SD=12.56) on the Nursing Professional Commitment Scale. Statistically significant relationships were found between nurses' motivation and altruism (p<0.01), motivation and professional commitment (p<0.001), altruism and professional commitment (p<0.001) scores. In addition, willingness to make an effort and maintaining professional membership, two sub-dimensions of professional commitment, were found to have a significant effect on motivation (p<0.001). Conclusion: As a result of the nurses' motivation, altruism and professional commitment levels are above medium. The nurses' motivation, altruism and professional commitment scores were related to each other.